2022
DOI: 10.1097/adm.0000000000001029
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Barriers to Sustained Engagement in Treatment With Medications for Opioid Use Disorder After Release From Incarceration

Abstract: BackgroundAlthough the burden of opioid use disorder is disproportionately high among persons who are incarcerated, medications for opioid use disorder are often unavailable in correctional settings. The Rhode Island Department of Corrections provides all 3 classes of medications for opioid use disorder to clinically eligible persons who are incarcerated. Despite a decrease in fatal overdoses among persons with recent criminal legal system involvement since the program's implementation, barriers to continued e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Third, participants reported feeling unprepared for release and suggested changes to improve the re-entry process for people with OUD, including improved treatment facilitation. Our findings build on the few prior studies examining the incarceration experience among people with OUD by evaluating the first 24-h post-release and re-entry preparation and focusing on individuals who are no longer incarcerated and engaged in methadone treatment [ 14 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Third, participants reported feeling unprepared for release and suggested changes to improve the re-entry process for people with OUD, including improved treatment facilitation. Our findings build on the few prior studies examining the incarceration experience among people with OUD by evaluating the first 24-h post-release and re-entry preparation and focusing on individuals who are no longer incarcerated and engaged in methadone treatment [ 14 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 85%
“…These barriers provide an opportunity for actionable policy and practice. For example, Kaplowitz et al found that participants suggested transportation options such as subsidized bus passes could facilitate treatment in the community post-release [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations